(untitled) (Philological Studies, 2021)
The article discusses the specifics and features of the functioning of the literary tradition in the novel “The Family” by Nina Fedorova in the context of phenomenon of literary centricity, which characterizes works of Russian émigré literati. In the work by the writer of the Russian abroad, there are many similarities with the novel by I.A. Goncharov “The Cliff”: at the level of the chronotope structure, individual images (the image of the Grandmother) and the image system as a whole, plot moves, motives, as well as stylistic devices. “The Family” is characterized by literary-centricity, it reproduces the atmosphere of the Russian manor culture and the topic of the Russian manor novel, the structural elements of Russian prose of the second half of the 19th century. Following the tradition allows the writer to keep in touch with Russian classical literature and Russian culture as a whole. At the same time, the recognition of the literary tradition reinforces the tragic register in the novel dedicated to the life of Russian emigrants of the first wave. The paper also considers some features of the poetics of the novel “The Family”: the role of symbolism in the figurative system of the work, the specifics of its spatial-temporal organization, the peculiarities of using metaphors, some characteristics of the narrative.